2016
DOI: 10.1016/j.jcis.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and degradation of Orange II by zinc aluminum layered double oxides

Abstract: In this work ZnAl-layered double oxide composites (LDO) were developed to remove organic dyes in wastewater by adsorption and photocatalysis. Various LDO composites were synthesized by adjusting synthetic parameters including the molar ratio of Zn to Al, and calcination temperature. LDO adsorption and photocatalytic properties for decomposition of organic dyes were also investigated. Orange II sodium salt (OrgII), an azo dye and water contaminant, was chosen as the model to investigate the properties of LDOs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 35 publications
(38 reference statements)
1
18
1
Order By: Relevance
“…(The change patterns of FT-IR spectra along with the adsorption time were given in Figure S9.) The successful intercalation of OrgII into LDH was also demonstrated by the shifting XRD pattern in our previous report [6]. …”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…(The change patterns of FT-IR spectra along with the adsorption time were given in Figure S9.) The successful intercalation of OrgII into LDH was also demonstrated by the shifting XRD pattern in our previous report [6]. …”
Section: Resultssupporting
confidence: 57%
“…The (100) peak of g-C 3 N 4 represents the heptazine unit with an interplanar separation of 0.66 nm and (002) peak represents the graphitic-like layer with an interlayer distance of 0.31 nm [25]. The XRD pattern of ZnO-LDH showed the presence of both ZnAl-LDH and ZnO [6]. The strong peaks at 31.2°, 33.8°, and 35.6° two theta found in ZnO-LDH sample are indexed to the diffraction of the (100), (002) and (101) planes of ZnO (JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The behavior of the materials in the UV-Vis diffuse reflectance indicates the photo-absorption ability. Previous studies showed that the narrowed-down band gap may lead to the enhancement of the responsiveness to visible light, as well as charge transfer and separation [36,37]. According to the literature, the band gap of the material can be calculated using the simplified Kubelka-Munk formula E g = 1240/λ (nm) [38], where λ is the wavelength corresponding to the absorption onset.…”
Section: Introductionmentioning
confidence: 99%